Unveiling the role of BON domain-containing proteins in antibiotic resistance - Sun, Shengwei; Chen, Jinju (Frontiers in Microbiology, 2025)
The alarming rise of antibiotic-resistant Gram-negative bacteria poses a global health crisis. Their unique outer membrane restricts antibiotic access. While diffusion porins are well-studied, the role of BON domain-containing proteins (BDCPs) in resistance remains unexplored. We analyze protein databases, revealing widespread BDCP distribution across environmental bacteria. We further describe their conserved core domain structure, a key for understanding antibiotic transport. Elucidating the genetic and biochemical basis of BDCPs offers a novel target to combat antibiotic resistance and restore bacterial susceptibility to antibiotics.